Eksistensi Saksi Ahli Dalam Sistem Peradilan Pidana Di Indonesia - Haryadi, Tobi; Zakaria, Zakaria (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2024)
Evidence is an important part of the trial process and is an important part of the trial of a case in court. The path of the accused is determined by evidence, which determines whether the accused actually committed the offense intended to be imposed on the accused who has been proven guilty. Basically, the purpose of the provisions of the Criminal Procedure Code on the need for expert testimony as evidence is to support certain elements of a crime, especially crimes that require testimony from someone who has special expertise related to the elements of the crime. This also means that expert testimony as a legitimate source of evidence cannot be considered the most important source of evidence.